A new case-depth estimation technique for induction-hardened plates based on dynamic response studies using laser Doppler vibrometer. (January 2015) - Misra, Mohan K; Bhattacharya, Bishakh; Singh, Onkar; Chatterjee, A
This article presents the effect of case depth due to surface hardening on the dynamic response of steel alloy–based circular plate. It indicates that such changes significantly affect the high-frequency response, especially, resonating modes and corresponding damping ratios of the plates. As the circular steel plates are quite rigid and hence the frequency responses are very small, a high precision three-dimensional laser Doppler vibrometer with a minimum velocity measurement capacity of 0.01 m/s is used to obtain the modal response. A statistical approach based on response surface methodology is then applied to obtain the correlation between the dynamic response of the system and the effective case depth. Also, another sensitive parameter termed as curvature change factor is introduced for the determination of the hardened layer thickness on the basis of laser Doppler vibrometer data. Thus, a new technique of condition monitoring of case-depth profile of steel plates based on non-contact dynamic response of the system has been established.